Predicting Tachypleus gigas spawning distribution with climate change in northeast coast of India - Pati, Siddhartha; Shahimi, Salwa; Nandi, Debabrata; Sarkar, Tanmay; Acharya, Satya N.; Sheikh, Hassan I.; Acharya, Dipti Kanta; Choudhury, Tanupriya; John, Akbar; Nelson, Bryan R.; Dash, Bisnu Prasad; Atan, Edinur Hisham (Polskie Towarzystwo Inzynierii Ekologicznej, 2021)
Species distribution models are used to predict ideal grounds, species range, and spatial shifts in an ecology over a span of time. With an aim to use Maximum entropy model (MaxEnt), presence records and pseudo-absence points are used to predict the Tachypleus gigas spawning activity for 2030 and 2050 in northeast India. The bearings of sixty T. gigas spawning grounds identified in 2018 were inserted into ArcGIS v.10.1. Meanwhile, 19 environment variables were inserted into MaxEnt v. 3.3.3, before the model performance was tested using receiver operational characteristics and area under curve (AUC). With an AUC of 0.978,85% was achieved for isothermality (bio3) and 74% for temperature (x̄= average) of the wettest quarter (bio8), all of which were inserted into ArcGIS to produce spatial maps. Although we learnt that T. gigas are still spawning in Odisha in 2030 and 2050, their distribution range is predicted to shrink due to the coastal morphology change. The climate conditions in Odisha revolve with the monsoon, summer and winter seasons from which, temperature variations do not only influence the annual absence/presence of spawning adults but also, the survival of juveniles in natal beaches. The use of MaxEnt offers novelty to predict population sustainability of arthropods characterized by oviparous spawning (horseshoe crabs, turtles, terrapins and crocodiles) through which, the government of India can take advantage of the present data to initiate the coastal rehabilitation measures to preserve their spawning grounds.